Quality assessment of a decoction of Sesamum indicum L. and Nigella sativa L.: Polycystic ovary syndrome - Deepthika, S.H.K.; Karunagoda, K.P.K.R.; Perera, P.K.; Arawwawala, L.D.A.M. (Asian Journal of Pharmacognosy, 2022)
Decoction prepared from N. sativa, and S. indicum can be used to treat oligo/anovulation, a primary sign of PCOS. Up to date no scientific experiments were carried out to access the quality of this decoction. Therefore, an attempt was made to evaluate the quality of the decoction made from N. sativa seeds and S. indicum seeds in terms of (a) phytochemical analysis (b) antioxidant activity (c) microbial limits (d) heavy metal limits and (e) development of TLC fingerprints using standard protocols. Results revealed that except flavonoids, other phytochemical constituents such as phenols, tannins, alkaloids, saponins, steroids, terpenoids, monoterpenes, sesquiterpenes and cardiac glycosides were present in the decoction. Total phenolic content of the decoction was 3.38 ± 0.07 mg gallic acid equivalents/g of extract and exhibited dose dependent (R2 = 0.979) scavenging activity towards 1-diphenyl-2-picryl hydrazyl (DPPH) radicals. IC50 value of the decoction was 850.5±30.2 µg/mL for the DPPH assay. Escherichia coli and Coliforms were not detected whereas yeasts & moulds and Staphylococcus aureus were present (less than 10 colony forming units (CFU) per 1 ml of the decoction). Moreover, heavy metals such as Hg, As, Cd and Pb were not detected in the decoction. Further, TLC fingerprint profile was developed for the decoction and visualized the spots under UV light and calculated the Rf values of each spot. In conclusion, reported phytochemicals and antioxidant properties may be responsible for the remedy of Polycystic Ovary Syndrome while absence of harmful microbes and heavy metals are the indication of the safety of the decoction.
Keywords: Antioxidant; Nigella sativa; Polycystic Ovary Syndrome; Sesamum indicum